KONTRIBUSI KEBUN PLASMA TERHADAP KEUNTUNGAN KEBUN NGABANG PT PERKEBUNAN NUSANTARA XIII (Persero) - Simbolon, Amran B; Yurisinthae, Erlinda; Suyatno, Adi (Jurnal Social Economic of Agriculture, 2013)
The purpose Of this study is to know how much of Contribution plasma estate concerning to Profit Ngabang Estate of PTP Nusantara XIII (Persero). Methods of reserch conducted is case research. Case researach is commit direct relationship between variable accourding to cause effect. The methods that use in this research is common size. Its making over number in loss/Profit balance become percentage. Database that use in this reasearch from accounting report of PT Perkebunan Nusantara XIII (Persero) from 2007 to 2012 at Ngabang estate. Ngabang estate have 31,7% of plasma estate and 68,3% inti esatate. The age of palm oil estate with have average 29 years old. According result of research plasma estate have a negatif relation to profit of Ngabang esatate PT Perkebunan Nusantara XIII (Persero) with percentage -161,91%. Its cause some factor, first advantage of amortisasi, second low productivity of palm oil caused the age too old. Third, Prices of plam oil comodity lower with the result next year must be relationship between plasma estate and inti estate has been loss. Beside that have suggestion the palm oil must be replanted and formation of Private managemet in plasma estate. Key Words : Contribution, Plasma, inti, Profit